Asosiasi Keragaman Growth Hormone Secretagogue Receptor (GHSR | Hin6i) terhadap Bobot Karkas Ayam Kampung pada Umur 12 Minggu - Syaikhullah, G.; Darwati, S.; Sumantri, C. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2017)
This study aimed to identify the GHSR genes polymorphism in chickens and to analyze the association of these genes on carcass weight and commercial cuts in chicken. A total of 60 local chickens (33 hen and 27 roosters) was used in this study. The chickens were bred in the colony cages and given full time access (ad libitum) to the commercial feed. The PCR-RFLP method was used to analyzed the gene polymorphism. The Hin6I was used as a restriction enzyme. The genotype frequency, allele frequency and Hardy Weinberg equilibrium were analyzed in this study. The phenotypic characteristics (body weight, carcass weight, breast weight, thigh weight, drumstick weight, wing weight and back weight) were analyzed using T test. The result showed that there were two genotypes (CT and TT) found in kampung chickens. The frequency of CT and TT genotype were 0.317 and 0.683, respectively. The value of Ho and He were 0.317 and 0.267 respectively. This population was not equal according to Hardy Weinberg equilibrium analysis. The GHSR gene polymorphism was significantly associated (P<0.05) with body weight, carcass weight, breast weight, thigh weight, drumstick weight, wing weight and back weight. The TT genotype was higher than CT genotype on all traits. The locus of GHSR|Hin6I could be used as a marker associated selection (MAS).